2000
DOI: 10.1091/mbc.11.4.1257
|View full text |Cite
|
Sign up to set email alerts
|

The PC6B Cytoplasmic Domain Contains Two Acidic Clusters That Direct Sorting to Distincttrans-Golgi Network/Endosomal Compartments

Abstract: The mammalian proprotein convertases (PCs) are a family of secretory pathway enzymes that catalyze the endoproteolytic maturation of peptide hormones and many bioactive proteins. Two PCs, furin and PC6B, are broadly expressed and share very similar cleavage site specificities, suggesting that they may be functionally redundant. However, germline knockout studies show that they are not. Here we report the distinct subcellular localization of PC6B and identify the sorting information within its cytoplasmic domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…Nterminal sequencing confirmed that this cleavage occurs at the site 42 RLPR 45 2 of pro-BACE sulfated at one or more of its carbohydrate moieties. The observations that sulfation of sugars occurs in the TGN (32) and that PCs, except perhaps PC5-B (34), are active only in this compartment or beyond indicated that processing of pro-BACE to BACE occurs either in the TGN or in post-TGN vesicles. This conclusion is consistent with those of Huse et al (40) who recently reported that BACE F is rapidly and efficiently transported to the Golgi apparatus and to a distal secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Nterminal sequencing confirmed that this cleavage occurs at the site 42 RLPR 45 2 of pro-BACE sulfated at one or more of its carbohydrate moieties. The observations that sulfation of sugars occurs in the TGN (32) and that PCs, except perhaps PC5-B (34), are active only in this compartment or beyond indicated that processing of pro-BACE to BACE occurs either in the TGN or in post-TGN vesicles. This conclusion is consistent with those of Huse et al (40) who recently reported that BACE F is rapidly and efficiently transported to the Golgi apparatus and to a distal secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Signals based on di-Leu and/or acidic residues have been shown for other proteins, including sortilin, low density lipoprotein receptor-related protein 3 (LRP3), cation-independent mannose 6-phosphate receptor (CI-M6PR), cation-dependent mannose 6-phosphate receptor (CD-M6PR), ␤-site APP-cleaving enzyme 2 (BACE2), p55 tumor necrosis factor receptor 1 (TNFR1p55), furin, and PC6B (43)(44)(45)(46)(47)(48). In these other proteins, the acidic cluster is usually found upstream of the di-Leu motif, which is usually near the C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were confirmed by DNA sequencing. The expression vectors for furin were constructed as described previously (11,21,22). ␣1PDX was described previously (32).…”
Section: Rprrakrmentioning
confidence: 99%